2010
DOI: 10.1007/s10008-010-1032-x
|View full text |Cite
|
Sign up to set email alerts
|

Oriented immobilization and electron transfer to the cytochrome c oxidase

Abstract: Direct electron transfer to cytochrome c oxidase (CcO) is investigated as a function of packing density of the surface layer. This is varied by the surface concentration of chelator molecules when the enzyme is immobilized on the electrode using the his-tag technology. Chelator molecules with a terminal nitrilotriacetic acid group are synthesized ex situ in contrast to in situ synthesis used in a previous work. Self-assembled monolayers of the chelator mixed at different mole fractions with a dilution molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…Dithiobis (nitriloacetic acid butylamidyl propionate) (short: DTNTA) DTNTA was synthesized as described [18], briefly N-(5-amino-1-carboxypentyl) iminoacetic acid (ANTA) was coupled to dithiobis (N-succinimidyl propionate) (DTSP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dithiobis (nitriloacetic acid butylamidyl propionate) (short: DTNTA) DTNTA was synthesized as described [18], briefly N-(5-amino-1-carboxypentyl) iminoacetic acid (ANTA) was coupled to dithiobis (N-succinimidyl propionate) (DTSP).…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization of the protein was performed as described [18]. Briefly CcO from Rhodobacter sphaeroides with a his-tag engineered to the C-terminus of subunit II was expressed and purified according to Hiser et al [19].…”
Section: Immobilization Of the Proteinmentioning
confidence: 99%
“…Our ptBLM system has the further advantage that a thin gold layer to be used as an electrode can be placed on top of the ATR crystal of an IR spectrometer thus providing the means for coupled EC/FTIR studies. When the gold electrode is further provided with a nano-particulate surface, surface-enhanced infrared-absorption spectroscopy (SEIRAS) can be employed controlled by EC [13,[19][20][21]. This methodology had proved very useful in the past in our titration studies of the CcO as well as time-resolved (tr-) SEIRAS studies of CcO and the photosynthetic reaction center (RC) of R. sphaeroides.…”
Section: Schematicmentioning
confidence: 98%
“…SEIRAS studies in an anaerobic environment [13,[19][20][21][22] had shown that the CcO could be converted reversibly into the fully reduced state. This state is necessary as a starting point for measurements under aerobic conditions, thus enabling the enzyme to undergo enzymatic oxidation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(Friedrich, Robertson et al 2008;Nowak, Schach et al 2009;Schach, Nowak et al 2010) For this purpose the bc 1 complex from the yeast Saccharomyces cerevisiae was adsorbed on a monolayer of cysteamine (CA) self assembled on template stripped gold (TSG) and alternatively the top plane of a silver rod modified with silver nanoparticles (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%